2003
DOI: 10.1177/002204260303300102
|View full text |Cite
|
Sign up to set email alerts
|

UNCOPE: A Brief Substance Dependence Screen for Use with Arrestees

Abstract: a clinical psychologist, has developed clinical assessment instruments for over 25 years and has served on accreditation panels for corrections based behavioral health programs. He provides training and technical assistance to states and organizations and is Clinical Associate Professor of Community Health at Brown University. Dana E. Hunt, Ph.D., a sociologist with over twenty-five years of experience in drug research, has conducted studies on methadone, HIV programming, experimental testing of non-traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…The fi rst 9 items with fi ve response alternatives each were coded 0, 1, 2, 3, or 4, and items 10 and 11 with three response alternatives were coded 0, 2 or 4, giving a maximum score of 44 points. 2 For validatory diagnosis of harmful use/substance abuse and dependence according to both ICD-10 and DSM-IV, the Swedish translation of Chapter 12 of the Schedules for Clinical Assessment in Neuropsychiatry (SCAN), Version 2.1 [6,7] , was chosen as a 'gold standard' interview schedule. Diagnoses were obtained using computer algorithms [8] .…”
Section: Measures and Scoringmentioning
confidence: 99%
“…The fi rst 9 items with fi ve response alternatives each were coded 0, 1, 2, 3, or 4, and items 10 and 11 with three response alternatives were coded 0, 2 or 4, giving a maximum score of 44 points. 2 For validatory diagnosis of harmful use/substance abuse and dependence according to both ICD-10 and DSM-IV, the Swedish translation of Chapter 12 of the Schedules for Clinical Assessment in Neuropsychiatry (SCAN), Version 2.1 [6,7] , was chosen as a 'gold standard' interview schedule. Diagnoses were obtained using computer algorithms [8] .…”
Section: Measures and Scoringmentioning
confidence: 99%
“…Previous research adapting the UNCOPE for the ADAM found that UNCOPE items demonstrated good discrimination for drug or alcohol misuse and dependence (Hoffman et al, 2003). In this analysis, separate measures are provided for alcohol and illicit drugs.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The DUDIT is presented on one page in a userfriendly graphic design with 11 items on the front page; the back page shows a list of illicit drugs in seven categories, followed by commonly abused sedatives, hypnotics, and analgesics. Several other instruments are available for the initial assessment of drug problems: the self-report 10-item Drug Abuse Screening Test (Skinner, 1982) or the six-item UNCOPE (Hoffman, Hunt, Rhodes, & Riley, 2003), as well as brief screening interview schedules such as CAGE-AID (Brown & Rounds, 1995) or Alcohol, Smoking and Substance Involvement Screening Test (ASSIST; Ali et al, 2002). 1 The DUDIT has three main advantages over these other instruments.…”
Section: Introductionmentioning
confidence: 99%